Lupus Antibody Mimicking Reduced Plasmatic Coagulation in a Patient With Atrial Fibrillation and Ischemic Stroke - Huseynov, Aydin; Haselmann, Verena; Kittel, Maximillian; Bertsch, Thomas; Alonso, Angelika; Neumaier, Michael; Borggrefe, Martin; Hoffmann, Ursula (Frontiers in Neurology, 2020)
Background: Lupus anticoagulant (LA) owns procoagulant properties in vivo and prolongs phospholipid-dependent clotting times in vitro. The increased in vitro clotting time can be misinterpreted as a bleeding disorder. In some cases, it is necessary to differentiate LA-associated in vitro changes from in vivo coagulation factor deficiency. In this case, we used different laboratory testing in a patient with ischemic stroke and reduced prothrombin time (PT) to identify an in-vitro effect of LA excluding an in-vivo bleeding disorder. Methods: The activity of various coagulation factors was evaluated both with recombinant thromboplastin Innovin (Siemens Healthcare) and reagent tissue extracted thromboplastin Thromborel® (Siemens Healthcare). Moreover, 1:1 plasma mixing test with standard plasma was performed. In order to exclude the interaction of tromboplastin and LA thromboplastin an independent global coagulation test, thromboelastography was used. Diluted-Russel-Viper-Venom (dRVVT) assay was applied to detect the presence of LA detection. Results: The activity of several coagulation factors measured with recombinant thromboplastin Innovin (Siemens Healthcare) showed a reduced activity of the following coagulation factors: Factor V (20.9%), Factor VII (23.8%), Factor X (19.7%) and Prothrombin Time (PT) (27.6%). Re-assessment of the factor’s activity with another reagent tissue extracted thromboplastin Thromborel® (Siemens Healthcare) showed an increase of PT/INR and factor’s activity in comparison to thromboplastin reagent Innovin: Factor V (77%), Factor VII (45.4%), Factor X (19.7%) and PT (59.1%). Plasma mixing study with 1:1 standard plasma revealed reduced (<50%) normalisation of PT as well as coagulation factors activity confirming a LA-inhibitor in the patient plasma. Diagnostic LA testing was also performed with dRVVT assay showing a significantly prolonged (112.8 sec) test time. Thromboelastography revealed no abnormalities. Conclusions: Different thromboplastin reagents and plasma mixing tests as well as thromboplastin independent coagulation tests may be helpful to differentiate LA and in vitro changes from in vivo factor deficiency in patients with LA.